Psychometric Properties of the Brazilian Version of the Sport Anxiety Scale-2 - Silva-Rocha, Viviane Vedovato; de Sousa, Diogo Araújo; Osório, Flávia L. (Frontiers in Psychology, 2019)
Competitive anxiety is an emotional reaction, manifested at a somatic and/or cognitive level, that regularly appears before or during sports competitions and can have a significant impact on an athlete’s performance. In view of the scarcity of validated instruments available for the evaluation of the competitive-anxiety trait in the Brazilian context, this study aimed to investigate the psychometric properties of the Sport Anxiety Scale-2 (SAS-2). For this, the sample was composed of 238 professional and amateur athletes from 13 years of age and older who practice different sports modalities. Confirmatory factor analysis results demonstrated adequate fit indices of the original three-factor theoretical model of the SAS-2 after adding a correlation between the errors of items 6 and 12 of the somatic anxiety subscale (CFI= 0.97, TLI= 0.96, RMSEA= 0.08, WRMR= 1.04). For convergent and divergent validity, the SAS-2 subscales presented positive and strong correlation coefficients with the CSAI-2R (r= 0.52 - 0.82), weak to moderate with the STAI-T (r= 0.49 - 0.59), weak with the SPIN (r= 0.29 - 0.41) and weak to moderate with the PHQ-9 (r= 0.49 - 0.56). SAS-2 was also able to discriminate among participants with and without social anxiety, general trait-anxiety and depressive symptoms, attesting its discriminant validity. According to the ROC curve analysis, the cutoff point at a score of 29 optimally balanced sensitivity (0.74) and specificity (0.82). The internal consistency (α= 0.73 - 0.86) and the test-retest reliability (ICC= 0.73 - 0.80) were satisfactory. In view of the results obtained, it was concluded that the Brazilian version of SAS-2 exhibited satisfactory psychometric performance and could be used in the Brazilian context.